CHANGES MONITORING IN SOME BLOOD BIOCHEMICAL PARAMETERS IN THE PHARMACOTHERAPY OF THE PATIENTS WITH DEPRESSIVE DISORDERS - Eleonora Aslibekovna Manvelyan; Svetlana Armaisovna Stepanyan (Современная наука и инновации)
The largest number and most representatives of other ethnic Slaivic women received Аmitriptylinum and Relanium. The longest was treated at Azafenum of Nogai women, the drug of choice for them was Grandaxinum, they were appointed by the smallest amount of Amitriptylinum and Relanium. The lowest dose course of Azafenum and Grandaxinum were in Armenian women.